C-Reactive Protein Level and its Relationship with Suicide Risk and Alexithymia among Newly Diagnosed, Drug-Naïve Patients with Non-Affective Psychosis. (January 2013) - De Berardis, D.; Conti, C.M.; Marini, S.; Serroni, N.; Moschetta, R.S.; Carano, A.; Valchera, A.; Iasevoli, F.; Fornaro, M.; Perna, G.; Di Iorio, G.; Martinotti, G.; et al.
The aim of the present study was to evaluate C-Reactive Protein (CRP) levels in newly diagnosed drug-naïve patients with non-affective psychosis, testing the hypotheses that in such patients serum CRP levels would be higher than in healthy controls and related to more severe psychopathology, suicide risk and alexithymia. CRP levels of 30 adult patients and 30 sex- and age-matched healthy controls were evaluated. Patients were tested with the Scale of Suicide Ideation (SSI), the Toronto Alexithymia Scale (TAS-20), the Scale for the Assessment of Positive and Negative Symptoms (SAPS and SANS) and the Calgary Depression Scale for Schizophrenia (CDSS). Higher suicide risk patients showed higher CRP levels than lower suicide risk patients and healthy controls. Moreover, such patients showed higher SAPS, SANS and CDSS scores than lower suicide risk patients. In linear regression model, CRP was significantly associated with higher SSI and TAS-20 scores. The results of the present study support the notion that CRP, suicide risk and alexithymia are strictly linked in newly diagnosed, drug-naïve patients with non-affective psychosis, independently of depressive symptoms or general psychopathology. Limitations are discussed.